KONSEP PENDIDIKAN AKHLAK ANAK MENURUT AL-QUR’AN DAN RELEVANSINYA DENGAN PENDIDIKAN AGAMA ISLAM - Muhammad Arroyan; M. Ali Ghufron (PT. Intelek Cendikiawan Nusantara, 2024)
Character education is a process of developing human nature that is based on and flavoured by the values of Islamic teachings. Moral education is a tool that provides clear instructions on how he should live and act according to his nature. Luqman Al-Hakim is a figure that the Qur'an uses as an example in moral education. Luqman provides guidance to parents and educators regarding the concept of moral education that must be taught to children. This research aims to: (1) to know the concept of children's moral education according to Surah Luqman verses 12-19, (2) to know how the relevance of the concept of children's moral education according to Surah Luqman verses 12-19 with Islamic religious education. Using qualitative research methods with the type of library research (library reseach). Analysed using the tafsir method, namely the tahlili (analytical) tafsir method. In this technical analysis, researchers tried to analyse books related to children's moral education in the family and the interpretation of the text of the books of interpretation of Surah Luqman verses 12-19. The results showed that, (1) the concept of children's moral education in Surah Luqman verses 12-19 contains three aspects, first, creed education contains aspects of monotheism which contains the prohibition of shirk. Second, sharia education contains aspects of worship, namely prayer. Third, social morals education includes, doing good to parents, charity ma'ruf nahi munkar, prohibition of being arrogant, haughty and the command to walk politely and speak softly. (2) its relevance to Islamic religious education, first, the curriculum, namely: (a) orientated to the development of students, social environment and the development of science and technology. The second aspect of the material, relevant to the subject of akidah, the third aspect of the goal, the purpose of moral education in Surah Luqman verses 12-19 is to form a human being with noble character towards God, self, and society. Keywords: Moral Education, Parents, Luqman Al-Haki m